EP300 Minimally invasive versus open-way surgery in early stage Cervical Cancer: SENTICOL I and SENTICOL II three years follow up. (1st November 2019) - Guani, B; Balaya, V; Magaud, L; Lecuru, F; Mathevet, P; Group, SENTICOL
Abstract : Introduction/Background: The LACC trial has recently assessed the impact of surgical approach on oncological outcomes in early-stage cervical cancer and found better outcomes in favor of open-way. In this study, we propose to assess this impact through data analysis of 2 French multicenter prospective cohort. Methodology: We analyzed the data of patients who participated in the prospective study SENTICOL I and SENTICOL II. We analyzed the disease-free survival (DFS) and the overall survival (OS) at 3 years in consideration of surgical access: laparotomy (LPT), laparoscopy (LPS), assisted vaginal laparoscopy (vaginal-assisted LPS) and vaginal. We included only patients with final FIGO 2009 stage IA1 with positive lymph-vascular invasion, IA2 and IB1. We considered age, type of cancer, stage, grade, tumor size, stromal invasion, lymph-vascular invasion, lymph nodal status, preoperative brachytherapy, and adjuvant therapy. The type of surgery was simple or radical hysterectomy and trachelectomy with sentinel lymph node biopsy alone or sentinel lymph node and lymphadenectomy. 3 years follow-up was analyzed with recurrence rate, localization of recurrence and survival rate. Results: In total, 257 patients were operated by hysterectomy or trachelectomy with a follow up of 3 years. Eighteen patients had recurrences with a global 3-years DFS at 93%. We found a statistically significant decrease of DFS in patients operated by LPT. In particular, among the 191 radical hysterectomies, patients who underwent surgery by LPT had a significant DFS decrease in comparison with minimally invasive surgical approach, especially with vaginal-assisted LPS (p=0, 03). Moreover, only age higher than 70 years influenced the risk of recurrence at 3 years (p<0, 01). Conclusion: Unlike the LACC trial results, our French multicenter prospective studies showed better oncological outcomes in patients operated by minimally invasive surgery. Age is confirmed to be a significant risk factor, as previously suggested in our recent article. Disclosure: Nothing to disclose.